Developing and Examining the Effectiveness of a Cognitive Behavioral Therapy-Based Psychoeducation Practice for Reducing Obsessive-Compulsive Symptoms in Adolescents: A Mixed-Methods Study With a Turkish Sample - Şimşek, Mustafa Kerim; Seçer, İsmail (Frontiers in Psychology, 2022)
This study set outs to develop a cognitive behavioral therapy (CBT)-based psychoeducation practice aimed at reducing obsessive-compulsive symptom levels in adolescents in Turkey and to test its effectiveness with a mixed-methods study. After the study was constructed as a pretest-posttest control group experimental application consisting of qualitative stages. Experimental application of the study was carried out with high school students in Turkey. In the sampling process, the schools where the study will be carried out were determined with the cluster sampling method, experimental and control groups were formed with 30 students with high OCD symptoms in these schools, and the developed CBT-based psychoeducation application was applied to the experimental group for 12 weeks. Quantitative data were collected through the “Child Version of the Obsessive-Compulsive Inventory,” and normality analyzes, t-test for dependent samples and Single Factor Analysis of Covariance were used for the analyzes. Qualitative data of the study were collected through document review, session evaluation forms and semi-structured interview protocol, and content and descriptive analysis techniques were used in the analysis. As a result of the study, it was concluded that the developed CBT-based psychoeducation application was an effective approach in reducing OCD symptoms in the Turkish adolescent sample, except for the neutralizing dimension. It was also determined that the findings obtained from the analysis of the obtained during the application and the interviews after the application also are parallel with the findings obtained by quantitative methods, and the qualitative and quantitative findings adequately explained the quantitative documents findings.